Taxation with a Grain of Salt: The Long-Term Effect of Fiscal Policy on Local Development - Tommaso Giommoni; Gabriel Loumeau (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the long-term effect of taxation on economic geography and development. We rely on a unique natural experiment in place during France's ancien régime: the salt tax. Introduced in the late 13th century and abrogated by the French Revolution in 1789, the salt tax was not uniformly levied across the French kingdom as its rate varied discontinuously in space. Using a series of rich and original historical data at regular time intervals and very fine spatial resolution since the fifteen century, we estimate a Spatial RDD model. We find that these exogenous tax rate differentials have had large effects on economic geography and development. These effects are, then, confirmed in a DiD analysis, that studies a very large time span (1400-1900 using regular intervals of 25 years) and documents the absence of pre-trends. Most of the effects can still be observed today in population density, firm density, and local average income.
Keywords: H20; N33; O23; J61; 330; taxation; long-term; economic georgraphy; development; spatial discontinuity; salt tax